Penggunaan Video Animasi DESI (Deskriptif, Edukatif, Smart dan Interaktif) Mengenai Sistem Pembayaran Shopee Pay Later dalam Pandangan Ekonomi Islam sebagai Sarana Edukatif bagi Mahasiswa - Ani Nur Aeni; Dwina Aprilia; Nur Amalia Putri; Adelia Afriyanti (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This study aims to determine the Shopee Pay Later payment system on consumer behavior from shopping online in the view of Islamic economics. In this research method using a quantitative approach derived from primary data that has been collected from respondents. The data collection technique used in this study is that respondents are given a series of questions which are usually called questionnaires, which are then filled out by respondents who meet the criteria determined by the researcher. This survey was attended by 55 students of the Elementary School Teacher Education study program at the Indonesian University Of Education. The findings of this study indicate that the strategy has a substantial positive or negative impact on consumer behavior in online purchases at Shopee Pay Later and consumer behavior in the Islamic view. In this case, you have to be careful when using Shopee Pay Later because if you overdo it, you will ensnare yourself. In Islam the process of debt and receivables must be avoided from usury and other harmful things. Based on the analysis, this research shows that Islam commands all humans, especially Muslims, to buy something according to their needs. It is suggested that Muslims regulate their consumption, which means that their consumer spending should not exceed their income, resulting in extravagant behavior. Muslims on the other hand, are not allowed to limit their spending as this will lead to destruction.